Cost-Benefit Analysis of Nano Coating on Ceramic Insulators on Leakage Current Characteristics - Pratama, Bagus Ardita (Indonesian Journal of Innovation and Applied Sciences (IJIAS), 2025)
Ceramic insulator components have high popularity because the majority of electrical distribution systems in Indonesia use ceramic insulators. Ceramic insulators have advantages in mechanical strength, but the nature of the surface material makes it easy to absorb water, which can accelerate aging and increase leakage current when used in high-pollution areas. This research will test the effect of salt and fly ash contaminants on the leakage current characteristics of ceramic insulators. Furthermore, it will be tested the effect of nano coating on the leakage current characteristics of ceramic insulators. Tests were conducted to analyze the leakage current characteristics on the insulator surface due to the influence of contaminants by varying the ESDD and NSDD values of contaminants with light, medium, heavy, and very heavy categories on the ceramic insulator surface. The results show that the higher the NSDD level and ESDD level of salt and fly ash contaminants, will increase the leakage current value. The test results of nano-coated ceramic insulators prove that they can reduce the value of leakage current. In testing ceramic insulators coated with nano coating materials contaminated with salt with a very heavy pollutant category, it is proven that the leakage current value is reduced by 23.5%. Testing ceramic insulators coated with nano coating materials contaminated with fly ash with a very heavy pollutant category proved that the leakage current value was reduced by 23.7%. Benefit-cost analysis is used to assess whether the nano-coating project on ceramic insulators is feasible or not feasible. The results of the analysis show that the Benefit Cost Ratio (BCR) value is obtained from the total present value benefit divided by the total present value cost, so that the result is 1< or more than one. The nano-coating project on ceramic insulators from the BCR parameter is feasible to implement.